2019
DOI: 10.3390/en13010029
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Response Quality Index for Assessing the Mechanical Condition of Transformer Windings

Abstract: Frequency response analysis (FRA) is a popular method for assessing a transformer’s mechanical condition. The paper proposes a new method for interpreting the frequency response measurement results. The currently used numerical indices only give one value, which may be misleading in the analysis, while the proposed frequency response quality index (FRQI) tool analyses three separate features in the whole frequency range. The applied numerical calculations technique allows for estimations of not only the values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As a rule, in FDS alternating current tests, measurements are made at three points per decade [11,[50][51][52]. In this way, tests of power transformers have also been performed [53][54][55][56][57][58]. This is due to the very highly time-consuming characteristic of measurements at ultra-low frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…As a rule, in FDS alternating current tests, measurements are made at three points per decade [11,[50][51][52]. In this way, tests of power transformers have also been performed [53][54][55][56][57][58]. This is due to the very highly time-consuming characteristic of measurements at ultra-low frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we propose utilizing the quality indicator (QI), whose definition considers the similarity of shapes, average values, and dynamics of changes between two compared datasets, based on their probabilistic properties [17].…”
Section: Quality Index For Assessment Of Complementary Fra and Vm Res...mentioning
confidence: 99%
“…FRA diagnostics using local assessment of quality indices is the actual scientific problem. The research in this field can be found in papers from top publishers [21,22] or from international conferences, for example [23]. An assessment based only on a single value returned by any numerical index may be misleading and result in a wrong interpretation of the measured FR data.…”
Section: Frequency Response Analysis and Assessment Of Measured Datamentioning
confidence: 99%